The nature and pollutant role of solids at the water-sediment interface in combined sewer networks - Chebbo, G.; Ashley, R.; Gromaire, M.C. (3rd International Conference on Sewer Processes and Networks (3rd SPN), 2002)
Solids at the water-sediment interface in combined sewers are known to be important for pollution potential during storm Washout via CSOs. They have been investigated in several studies, but nonetheless, little is known about the origins, build-up, transport and nature of these solids. From a review of current knowledge, it is apparent that whilst there is general agreement that these solids are largely organic and have high polluting potential, their modes of transport and definition are not generally agreed upon. It is possible that there may be several ‘‘types’’ of these solids, defined as either: ‘‘near bed solids’’ or ‘‘fluid sediments/dense undercurrents’’, possibly representing transport modes in flows with different ranges of ambient (dry weather) velocities and with differing sewerage layouts. Current knowledge is presented and new ideas for resolving the uncertainties regarding the nature, movement and effects of this material are outlined.